Diseño de un Procedimiento de Instalación, Implementación y Operación de un motor de arranque Delco Remy adicional para mejorar el rendimiento del encendido de un motor Generador Cummins industrial en la ciudad de Barranquilla. (2023)
Today, great care must be taken with the equipment used in the different processes, comply with its maintenance, because when measuring its performance we can realize that it is not giving the expected results; taking into account that with the technological revolution we must adapt, both the human resources, tools and equipment, for this, knowing the performance of the latter very well, we can say that the strategies were well implemented.